치아우식과 연관된 타액의 pH와 완충력 - 정순정; Soon Jeong Jeong; 윤미숙; Mi Sook Yoon; 임도선; Do Seon Lim; 정문진; Moon Jin Jeong; Sonja Apostolska; Mira Jankulovska; Dragana Angelova; Salvador Nares; et al. (Chiwisaeng gwahakoeji, 2006)
This study examined the relationship between the quantity of Streptococcus mutans and Lactobacillus spp. related to dental caries and the degree of acidity in saliva. A total of 240 saliva samples were taken from 80 subjects at the faculty of dentistry in Skopje, Macedonia. The saliva samples were taken by stimulating saliva production stimulation with paraffin chewing. However, no stimulation was applied when obtaining the samples used for measuring the pH. The data showed that in the caries group, S. mutans in 1 ml of saliva formed colonies with confluent growth (CFU > $10^6$ and $10^4-10^5$) in 100% of samples, whereas the Lactobacillus spp. formed colonies with confluent growth in 78.3%. In contrast, no colonies with confluent growth (CFU > $10^6$ and $10^5$) were found in the control group (with healthy intact teeth). In the caries group, the pH of the saliva was slightly acidic (pH = 5.90 - 6.50) and the buffering capacity was very low (below 0.7 ml of saliva per min). On the other hand, the pH of the saliva in the control group was neutral (pH 7.01 - 7.7) and the buffering capacity was high (over 1 ml of saliva per min). The increased number of S. mutans and Lactobacillus spp. in 1 ml of saliva (above $10^5$ CFU or more) from the CRT (Caries Risk Test, Vivadent, Liechtenstein) bacteria test can indicate an increased caries risk as well as slightly higher acidity of the saliva. Overall, these results reveal that the caries risk can be predicted by simply measuring the pH and buffering capacity of saliva, and can be used to monitor the effect of dental hygiene practices with the aim of preventing dental caries. 이 연구의 목적은 타액이 산성일때 치아우식과 연관이 있는 Streptococcus mutans 와 Lactobacillus spp.의 양을 조사하여 치아우식의 지표로 사용될 수 있는지를 관찰한 외국인을 대상으로한 임상결과이다. 총 240개의 타액 표본들은 마케도니아(Macedonia), 스코프에(Skopje)에 위치한 St Kiril- Metodi 치과대학병원에서 환자 80명으로부터 얻었다. 표본들은 사전의 파라핀 저작(씹기)법에 의해 타액을 자극하여 얻어졌으나, 타액의 pH의 결정을 위해서 다른 자극은 사용되지 않았다. 치아우식 집단의 타액 1 ml에서 S. mutans는 100%의 confluent growth (CFU > $10^6$와 $10^4-10^5$) 였으나, Lactobacillus spp.는 78.3%였다. 대조표본 집단(건강하고 손상되지 않은 치아를 가짐)에서, confluent growth (CFU > $10^6$와 $10^5$)를 가지는 colony는 발견되지 않았다. 이와 달리, 두 집단 모두(60 + 20)에서 타액의 pH와 타액의 완충력으로부터 얻어진 결과는 상호연관이 있었다. 치아우식집단에서, 타액의 pH 결과치는 약산성(5.90 - 6.50)이었고, 타액의 완충력 역시 매우 낮았다(0.7ml 이하). 한편, 대조표본 집단에서, 타액의 pH는 중성(pH 7.01 - 7.7)이었고 타액 완충력은 높았다(1ml 이상). CRT-bacteria 시험법으로부터 얻은 타액 1 ml내($10^5$ CFU 이상)의 S. mutans와 Lactobacillus spp.의 증가된 수는 타액의 산성과 약산성 pH의 결과처럼 치아우식위험을 증가시켰다. 따라서, 타액 pH법과 완충력 측정법은 치아우식 위험을 예측 할 수 있으며, 치아우식 예방을 위해 유용한 측정법으로 사용될 수 있을 것으로 사료된다.